NEGOTIATION OF IDENTITY: (RE)CONSTRUCTION AND (RE)POSITIONING OF SELF THROUGH LANGUAGE LEARNING - Isiki, Naho (Indonesian Journal of Applied Linguistics, 2013)
Abstract: Becoming competent in a language involves more than just academic success, but also multi-faceted aspects of self in a situated context. The core of the study is to explore a participant’s experience as a marginalized student in a Filipino American community and the trajectories of learning a foreign language over time and space. Narratives from the participant reflect his approach toward language learning (LL) as well as his motivation behind language learning. This study highlights the impact of foreign language learning experience upon the participant’s conflict, negotiation, and transformation of identity. Following his positioning analysis, the paper closely looks at how evaluation by other Filipinos within the community contributes to the participant’s ongoing (re)construction and negotiation of identity. How these evaluations encourage or impede his access to heritage language and culture is analyzed based on the participant’s use of reported speech. The paper explored whether or not LL can be a way of negotiating and gaining agency, as well as how LL helps a marginalized learner to choose where and how he wants to belong to. The paper also looks at how marginalization motivates language learning, through which the participant seeks to reposition himself. The study also examines how power relationship (marginalized student in a situated context) plays a role in the process of negotiation of identity and meaning-making of self. Results from this study conclude that through experiences in foreign language learning as well as negotiating meanings for being a Japanese as a Foreign Language (JFL) student, the participant gradually shifts to belong to a different community prior to his language learning experience in which he can practice agency and is no longer a marginalized member of his heritage community.